Spinal excitatory mechanisms of pathological pain - Kuner, Rohini (Pain, 2015)
An important property of the nociceptive system is its plasticity, ie, the ability to change in an experience-dependent manner, which is implicated in the transition from acute pain to chronic pathological pain. Disease-induced plasticity can occur at both structural and functional levels and manifests as changes in individual molecules, synapses, cellular function, and network activity. In this short review, the author discusses how synaptic plasticity may mediate pathophysiological alterations linked to chronic pain by virtue of shifting the balance between excitation and inhibition, with a particular emphasis on the spinal dorsal horn.
Gesehen am 03.06.2020